Kualitas Informasi Pilkada dalam Media Sosial dan Sikap Pemilih Pemula (Studi pada Pasangan Wali Kota Terpilih di Kota Cimahi) - Nuramalia, Reffina; Bajari, Atwar; Sugiana, Dadang (Jurnal Politikom Indonesiana, 2018)
The purposes of this research were to find the correlatio between information valance and information weight of the election information shared through social media with “beginner voters” attitude toward the elected mayor in Cimahi. The theory used of this research was Information Integration Theory that was proposed by Martin Fishbein. This research used quantitative approach with correlational method. Data collection tehnique was done by distributing questionnaires to 111 selected students of class XII SMAN 2 Cimahi from 154 students of the target population, with simple random sampling technique. The results showed as follows; there was a significance correlation between valance of election information shared through social media with “beginner voters” attitude toward the elected mayor in cimahi. There was a significance correlation between weight of election information shared through social media with “beginner voters” attitude toward the elected mayor in cimahi. So it can be concluded that there was a significance correlation between quality of election information shared through social media with beginner voters’ attitude toward the elected mayor in Cimahi. Keywords: Election, Social Media, Information Quality, Attitude, Beginner Voters